Analiza wpływu częstotliwości danych na rozkłady stóp zwrotu oraz na klasyfikację spółek giełdowych - Batóg, Barbara; Batóg, Jacek (Analysis of the influence of frequency of the data on distribution of rates of return and on the classification of firms from Warsaw Stock Exchange, 2006)
The values and coefficients of correlation of stock returns have significant influence on the results of modeling of phenomena on capital market. In the paper the authors tried to evaluate the influence of change of frequency of stock returns on their distributions, coefficients of correlation and classifications. It turned out that all above characteristics are very sensitive on frequency of data. Means, standard deviations, coefficients of correlation of stock returns and differences between classifications are greater for monthly than for daily data.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 263-270